2006
DOI: 10.1111/j.1600-6143.2006.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopulmonary Syndrome Increases the Postoperative Mortality Rate Following Liver Transplantation: A Prospective Study in 90 Patients

Abstract: Hepatopulmonary syndrome (HPS) is a frequent pulmonary complication of patients with end-stage liver diseases. HPS is diagnosed by hypoxemia and pulmonary vascular dilatation and is an independent risk factor of mortality. Orthotopic liver transplantation (OLT) is the only factor that modifies the natural course of HPS. Once patients with HPS have been transplanted, their long-term survival rate is similar to transplanted patients without HPS. Consequently, HPS is an indication of OLT whatever the severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 31 publications
7
64
1
1
Order By: Relevance
“…Schenk et al 44 have demonstrated that mortality in HPS correlated with the severity of hypoxemia and was independent of Child-Pugh classification. Schiffer et al 45 found no relationship between MELD score and IPVD among patients undergoing LT. Although not statistically significant, the finding of higher MELD and MELD-Na scores in our IPVD group supports the possibility of more severe liver disease in the IPVD group.…”
Section: Discussionmentioning
confidence: 97%
“…Schenk et al 44 have demonstrated that mortality in HPS correlated with the severity of hypoxemia and was independent of Child-Pugh classification. Schiffer et al 45 found no relationship between MELD score and IPVD among patients undergoing LT. Although not statistically significant, the finding of higher MELD and MELD-Na scores in our IPVD group supports the possibility of more severe liver disease in the IPVD group.…”
Section: Discussionmentioning
confidence: 97%
“…5,9 After the management guidelines for HPS were published, in which PA-a,O 2 ≥ 15 mmHg in liver disease patients with IPVD was deemed sufficient for confirmation of HPS, it was suggested that PaO 2 should no longer be a separate diagnostic criterion and should also become part of the classification of the syndrome, with prognostic significance. 5,59 HPS may therefore be classified as mild in cases of PaO 2 ≥ 80 mmHg, moderate in cases of PaO 2 < 80 mmHg or ≥ 60 mmHg, severe in cases of PaO 2 < 60 mmHg or ≥ 50 mmHg and very severe in cases of PaO 2 < 50 mmHg. 5 …”
Section: Arterial Gas Analysismentioning
confidence: 99%
“…61,[87][88][89] It should be stressed that this is a recent indication, since HPS was previously considered to be a contraindication for liver transplant surgery. 64 Because HPS may be an independent risk factor for worse prognosis among liver transplant candidates, 14,59 there is a current formal recommendation to prioritize transplantation for patients with the severe form of this syndrome. 18,22 However, each HPS case that is considered severe should be analyzed individually because of the high morbidity and mor-tality rates associated with this condition, both during surgery and during the postoperative period.…”
Section: Hps Treatment and Prognosismentioning
confidence: 99%
“…7,9,10 Low partial pressure of arterial carbon dioxide (PaCO 2 ) measurements are commonly found in patients with HPS Box 1 Treatments for hepatopulmonary syndrome.…”
Section: Pastor Is the Chief And E Schiffer Is A Principal Investimentioning
confidence: 99%